Early ovarian cancer: our view of the problem - K. I. Zhordania; S. V. Khokhlova (Опухоли женской репродуктивной системы, 2014)
The paper considers some pathogenetic aspects of ovarian tumor development, on the basis of which the authors recommend to perform more aggressive chemotherapy in patients with the so-called early stages of ovarian cancer.